PENERAPAN ARSITEKTUR MODEREN PADA PERPUSTAKAAN DAERAH PROVINSI GORONTALO - Arsyad, Khaeruddyn Abdul Gani; Mahanggi, Muhammad Rizal; Trumansyahjaya, Kalih (Universitas Negeri Gorontalo, 2022)
As a source of literacy, a library plays an essential role in developing the quality of human resources. Complete facilities and infrastructures will aid in the improvement of the quality of the human resources in an area. Gorontalo has a regional library, yet the facilities and infrastructures are poor and not in accordance with applicable standards under government regulations regarding National Standards for Provincial Libraries. This library’s planning aimed to obtain a design that complies with the mentioned standards and adequate facilities and infrastructure. The data collection method employed in this design was through field observation, which entails reviewing fields condition and collecting the data by interviewing relevant parties. The data was also collected by identifying aspects the could be applied in the design, including technical aspects and structuring design aspects under the criteria. The outcome was analyzed to develop a design concept based on the theme of Modern Architecture. The final step of design was a regional library that met all applicable criteria and was equiooed with infrastructures to support the needs of Gorontalo’s communities. The reports result was in the form of a design and its implementation towards the design of the Regional Library of Gorontalo Province.